Dynamic Response of Wheel-Rail Interaction at Rail Weld in High-Speed Railway - Boyang An; Ping Wang; Jieling Xiao; Jingmang Xu; Rong Chen (Shock and Vibration)
As a main part of continuously welded rail track, rail weld widely exists in high-speed railway. However, short-wave irregularities can easily initiate and develop in rail weld due to the limitation of welding technology and thus rail weld has been a main high-frequency excitation and is responsible for deterioration of track components. This work reports a 3D finite element model of wheel-rail rolling contact which can simulate dynamic wheel-rail interaction at arbitrary contact geometry up to 400 km/h. This model is employed to investigate dynamic response of wheel-rail interaction at theoretical and measured rail weld, including wheel-rail force and axle-box acceleration. These simulation results, combined with Quality Index (QI) method, are used to develop a quantitative expression, which can be easily applied for evaluating rail weld deterioration based on measured rail profiles and axle-box acceleration.